Women With a History of Primary Infertility and Increased Rates of Bilateral Oophorectomy. Issue 4 (7th October 2022) - Ainsworth, Alessandra J.; Sadecki, Emily; Zhao, Yulian; Weaver, Amy L.; Stewart, Elizabeth A.
Abstract : Women with a history of primary infertility have an increased risk of bilateral oophorectomy, and women with endometriosis-associated infertility have an increased risk of hysterectomy. Abstract : OBJECTIVE: To evaluate the association of primary infertility with subsequent bilateral oophorectomy and hysterectomy, using a population-based cohort of women with primary infertility and age-matched women in a referent group. METHODS: The Rochester Epidemiology Project record-linkage system was used to assemble a population-based cohort of women with primary infertility diagnosed between 1980 and 1999 (index date). Women were age-matched (±1 year) 1:1 to women without a history of infertility or hysterectomy at the index date (referent group). Cox proportional hazards models were fit to compare long-term risks of bilateral oophorectomy and hysterectomy, respectively, between women with infertility and women in the referent group. RESULTS: Among both groups of 1, 001 women, the mean age at the index date was 29.2±4.4 years. Median duration of follow-up was 23.7 years for both groups. Women with primary infertility were 1.7 times (adjusted hazard ratio [aHR] 1.69, 95% CI 1.22–2.33) more likely to undergo bilateral oophorectomy compared with women in the referent group. In a sensitivity analysis that excluded women with a diagnosis of infertility related to endometriosis and their matched referent group participants, this association persisted (aHR 1.50, 95% CI 1.06–2.14). Women with primary infertility did not have a significant increased risk of hysterectomy (aHR 0.98, 95% CI 0.79–1.23). However, risk of hysterectomy was increased in those with primary infertility related to endometriosis (aHR 1.94, 95% CI 1.12–3.34). We observed that women with primary infertility were more likely to undergo hysterectomy with bilateral oophorectomy. Women in the referent group were more likely to undergo hysterectomy with ovarian conservation. Few women in either group had isolated bilateral oophorectomy. CONCLUSION: Primary infertility, with and without a diagnosis of endometriosis, is associated with an increased risk of bilateral oophorectomy. In women with endometriosis-related infertility, there is an association with future hysterectomy. These findings represent important confounders in the evaluation of long-term health outcomes related to primary infertility.